Hard or Soft Governance? The EU’s Climate and Energy Policy Framework for 2030 - Oberthür, Sebastian (2019)
This article investigates the stringency of EU climate and energy governance along the soft-hard continuum as a key determinant of its ability to achieve its ambitions. It introduces four criteria for a systematic and differentiated assessment of the bindingness/stringency of legislative instruments and governance frameworks, namely: (1) formal legal status, (2) the nature of the obligations (substantive—procedural), (3) their precision and prescriptiveness, and (4) the means for effecting accountability and effective implementation. The application of this assessment framework to the EU’s Climate and Energy Policy Framework for 2030 in comparison with the preceding 2020 Framework and the international Paris Agreement on climate change demonstrates the added value of this approach. The focus is on regulations, adopted in 2018, regarding greenhouse gas emissions, renewable energy (RE), and energy efficiency as well as the surrounding framework for planning, reporting, monitoring, and enforcement. The EU’s 2030 Framework scores high on the four criteria. Despite implementing the comparatively soft Paris Agreement, it does not fall behind the stringency of the 2020 Framework, as the abandoning of binding national targets for RE is balanced by strengthened obligations to prepare national plans, long-term strategies, and regular progress reports, as well as the enhanced monitoring and supervisory powers of the European Commission. While actual delivery will not least depend on how the Commission will use its established and newly acquired powers and tools, the 2030 Framework reinforces EU interest in strengthening international climate governance under the Paris Agreement.